Analisis Pengaruh Variabel Makroekonomi terhadap Biaya Perjalanan Ibadah Haji - Nurunnasikin, Nurunnasikin; Indra, Indra; Afifah, Kuni (Penerbit Goodwood, 2024)
Purpose: This study analyzes the impact of macroeconomic factors such as exchange rates, global oil prices, and inflation on Hajj pilgrimage costs. Methodology: This is a qualitative study. Time-series data from 1980 to 2022 were used in this study. The data were analyzed using the VECM method. Results: The results show that, in the long run, exchange rates, crude oil prices, and inflation have a significant impact on the cost of Hajj. Limitations: Difficulty in obtaining annual data. This is a common limitation of research that relies on secondary data sources. Annual data may not be readily available or may be difficult to access. Contribution: One of the main contributions of this study is that it identifies factors that can affect the long-term cost of the Hajj pilgrimage. This information can be used by stakeholders to maintain the stability of the Hajj pilgrimage costs by considering these factors.